Negative refractive index anomaly characteristics of SRR hexagonal array metamaterials - Yan Soerbakti; Moh Danil Hendry Gamal; Zamri Zamri; Defrianto Defrianto; Romi Fadli Syahputra (Science, Technology, and Communication Journal, 2024)
Metamaterials possess distinct characteristics that make them very suitable for scientific investigation. This phenomenon's hallmark has left scientists perplexed and skeptical. Researchers have conducted numerous studies to explore the composition of one or more metamaterials. This project focused on the development of a linear-sequence metamaterial. Next, we examined the alterations in the optical characteristics of the metamaterial. The utilized frequency range is 0 to 9 GHz. We construct the hexagonal split ring resonance (SRR) metamaterial with a radius of 2.9 mm, consisting of one to four hexagonal SRRs. The findings revealed that the SRR hexagonal metamaterial structure had the highest negative refractive index value, reaching -9.33 in combinations of four hexagonal SRRs.